2010
DOI: 10.1074/jbc.c110.130013
|View full text |Cite
|
Sign up to set email alerts
|

Dynamin 2 Mutants Linked to Centronuclear Myopathies Form Abnormally Stable Polymers

Abstract: Mutations in the dynamin 2 gene have been identified in patients with autosomal dominant forms of centronuclear myopathy (CNM). Dynamin 2 is a ubiquitously expressed ϳ100-kDa GTPase that assembles around the necks of vesiculating membranes and promotes their constriction and scission. It has also been implicated in regulation of the actin and microtubule cytoskeletons. At present, the cellular functions of dynamin 2 that are affected by CNM-linked mutations are not well defined, and the effects of these mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 36 publications
(51 reference statements)
8
80
0
2
Order By: Relevance
“…Recent biochemical studies have indicated that some CNMcausing DNM2 mutations increase dynamin oligomer stability and GTPase activity (26,27). This was supported in vivo by either knockin or overexpression of the most common CNM-DNM2 patient mutation in mice, which induced CNM-like features at adulthood (28,29), indicating that the disease is not due to haploinsufficiency.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Recent biochemical studies have indicated that some CNMcausing DNM2 mutations increase dynamin oligomer stability and GTPase activity (26,27). This was supported in vivo by either knockin or overexpression of the most common CNM-DNM2 patient mutation in mice, which induced CNM-like features at adulthood (28,29), indicating that the disease is not due to haploinsufficiency.…”
Section: Introductionmentioning
confidence: 73%
“…Loss-of-function mutations in MTM1 and dominant mutations in DNM2 lead to CNM in human and CNM phenotypes in mice models (1,9). Moreover, biochemical analysis suggests several DNM2 CNM mutants increase DNM2 GTPase activity and oligomerization (26,27). Furthermore, overexpression of WT DNM2 by AAV or by miR-133a inhibition resulting in increased DNM2 expression promoted muscle defects and centralization of nuclei in mouse muscle (28,30).…”
Section: Discussionmentioning
confidence: 99%
“…Recessive BIN1-CNM is due to BIN1 loss of function and dominant DNM2-CNM is probably due to DNM2 gain of function (5,7,(15)(16)(17). We hypothesize that these 2 proteins are working antagonistically in the same pathway for muscle maturation and that reducing DNM2 expression might rescue the neonatal lethality observed in …”
Section: Bin1 Is Required In Skeletal Muscle For Perinatal Survivalmentioning
confidence: 99%
“…DNM2 is a large GTPase involved in membrane fission and endocytosis (13,14). Biochemical studies indicated that several DNM2 mutations causing CNMs increase dynamin oligomer stability and GTPase activity (15)(16)(17). Moreover, overexpression of WT or a DNM2-CNM mutation leads to CNM-like features in mice and perturbation of muscle and T-tubules in Drosophila (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study showed that specific CNM-related DNM2 mutations cause increased GTPase activity and promote dynamin oligomerization without altering lipid binding (32). Another study also showed that CNM-related DNM2 mutants enhance the stability of dynamin polymers without impairing their ability to bind and/or hydrolyze GTP (33).…”
Section: Figurementioning
confidence: 99%